The STRING database in 2017: quality-controlled protein-protein association networks, made broadly accessible - Szklarczyk, Damian; Kuhn, Michael; Bork, Peer (Nucleic acids research, 2017)
Abstract. A system-wide understanding of cellular function requires knowledge of all functional interactions between the expressed proteins. The STRING databas
Published: 18 October 2016
Gesehen am 22.06.2018